2013
DOI: 10.1073/pnas.1221216110
|View full text |Cite
|
Sign up to set email alerts
|

p63-expressing cells are the stem cells of developing prostate, bladder, and colorectal epithelia

Abstract: The tumor protein p63 (p63), and more specifically the NH2-terminal truncated (ΔN) p63 isoform, is a marker of basal epithelial cells and is required for normal development of several epithelial tissues, including the bladder and prostate glands. Although p63-expressing cells are proposed to be the stem cells of the developing prostate epithelium and bladder urothelium, cell lineages in these endoderm-derived epithelia remain highly controversial, and rigorous lineage tracing studies are warranted. Here, we ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
194
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(211 citation statements)
references
References 41 publications
11
194
0
1
Order By: Relevance
“…Additionally, co-activation of AR with the C-terminal domain of Gli2 regulates androgen-responsive genes in prostate cancer cells (41). Given the fact that p63-expressing basal cells are essential for prostate sphere formation and prostate development (21,35), future studies of whether and how p63 ϩ , CK5 ϩ , and CK8 ϩ and total number of cells in tubules from Kras(G12D)ϩARϩvector and Kras(G12D)ϩARϩshGli1/2 regenerated tissues was counted. The percentage of each type of cells was calculated.…”
Section: Ck5mentioning
confidence: 99%
“…Additionally, co-activation of AR with the C-terminal domain of Gli2 regulates androgen-responsive genes in prostate cancer cells (41). Given the fact that p63-expressing basal cells are essential for prostate sphere formation and prostate development (21,35), future studies of whether and how p63 ϩ , CK5 ϩ , and CK8 ϩ and total number of cells in tubules from Kras(G12D)ϩARϩvector and Kras(G12D)ϩARϩshGli1/2 regenerated tissues was counted. The percentage of each type of cells was calculated.…”
Section: Ck5mentioning
confidence: 99%
“…They induce different target genes (Dohn et al, 2001, Wu et al, 2003. DNp63 is fundamental for the maintenance of the stem and progenitor cells in stratified epithelial and glandular tissues (Pignon et al, 2013, Senoo et al, 2007. TAp63 has a role in female germ cell preservation (Suh et al, 2006), in protection against cancer metastasis (Melino, 2011, Su et al, 2010 and in senescence (Flores et al, 2005).…”
Section: P63: Targetsmentioning
confidence: 99%
“…Furthermore, using a lineage-tracing approach, Choi et al 7 demonstrated that basal and luminal cells in adult mouse prostates are independent self-sustaining lineages during prostate regeneration. However, using the same approach, other groups reported that in addition to unipotent luminal cells, basal cells can act as multipotent stem cells during prostate development or regeneration [8][9][10] .…”
mentioning
confidence: 99%